2017
DOI: 10.1038/s41598-017-08624-4
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-dependency of the association between systemic antioxidant potential and glaucomatous damage

Abstract: Systemic oxidative stress is thought to be an important factor in the pathogenesis of glaucoma. In particular, low systemic antioxidative capacity, which normally counters oxidative stress, may contribute to glaucoma. Thus, we investigated the association between biological antioxidant potential (BAP), a biomarker of systemic antioxidative capacity, and glaucoma severity in patients with open-angle glaucoma (OAG). This study included 480 eyes of 240 patients with OAG and 66 healthy control eyes. We measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
0
28
1
Order By: Relevance
“…Tanito et al found that there was no significant difference in dROMs between control and glaucoma groups 17 . In the current study, there were no control subjects, but in a previous study, we found that there were no significant differences in dROMs between controls and any of several OAG subgroups 10 . In the current study, moreover, there was a significant association between dROMs and age in the female OAG patients, but not in the male OAG patients.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…Tanito et al found that there was no significant difference in dROMs between control and glaucoma groups 17 . In the current study, there were no control subjects, but in a previous study, we found that there were no significant differences in dROMs between controls and any of several OAG subgroups 10 . In the current study, moreover, there was a significant association between dROMs and age in the female OAG patients, but not in the male OAG patients.…”
Section: Discussioncontrasting
confidence: 71%
“…Additionally, female hormones have an antioxidative effect. We previously found that in younger male patients, there was a relationship between reduced BAP and glaucoma severity, but that this relationship was absent in younger female patients 10 . However, after menopause, female subjects with low BAP are susceptible to changes in CH.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations